PL.20 Perineal Assessment and Repair E-Learning System (ePEARLS): An E-Learning Training Package to Improve Clinical Management of Perineal Trauma Following Childbirth. (26th April 2013) - Mahmud, A; Kettle, C; Bick, D; Rowley, C; Rathod, T; Belcher, J; Abdelmaguid, M; Ismail, K
Abstract : Background: Birth related perineal trauma can have a major impact on women's health. The correct assessment and repair of perineal injuries are procedures that require knowledge and skill. Currently, there is no agreement as to what constitutes an effective training programme. We produced and tested an interactive distance learning multi-professional training package called ePEARLS. This was developed as a tool for the delivery and assessment of perineal repair training in line with UK evidence based practise. Methods: The main aim of this project was to develop, refine and assess ePEARLS as a tool for the assimilation of knowledge and skill to clinicians involved in Intrapartum care. Using pre and post-training objective assessments for both knowledge and skill, we compared the effect of delivering training using ePEARLS compared to other training models in three independent multi-professional groups from three different maternity units. Results: Thirty-eight participants were involved in the study. Improvements in knowledge scores were marginally significant in all three groups. However, more marked improvements in skill scores were noted in response to the different training models. Conclusion: ePEARLS is the first multi-professional interactive perineal trauma management e-learning package that has been formally tested against other training models. The potential cost effectiveness of this package makes it far superior to other methods of delivering training and maintaining competency.